2017
DOI: 10.1177/0018720817738591
|View full text |Cite|
|
Sign up to set email alerts
|

Falls From Agricultural Machinery: Risk Factors Related to Work Experience, Worked Hours, and Operators’ Behavior

Abstract: Objective We investigated the risk factors for falls when egressing from agricultural tractors, analyzing the role played by worked hours, work experience, operators' behavior, and near misses. Background Many accidents occur within the agricultural sector each year. Among them, falls while dismounting the tractor represent a major source of injuries. Previous studies pointed out frequent hazardous movements and incorrect behaviors adopted by operators to exit the tractor cab. However, less is known about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 47 publications
4
26
1
1
Order By: Relevance
“…Agricultural exhibitions play an important role in the life of Italian small country towns, where they often combine amusement elements, breeding stock exhibitions and sports happenings, with lectures, seminars, and conferences. These features make this kind of agricultural exhibitions a suitable place for survey and data collection (Caffaro, Micheletti Cremasco, Roccato, & Cavallo, ; Cavallo, Görücü, & Murphy, ; Ferrari, Spinelli, Cavallo, & Magagnotti, ; Reichardt & Jürgens, ; Reichardt, Jürgens, Klöble, Hüter, & Moser, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural exhibitions play an important role in the life of Italian small country towns, where they often combine amusement elements, breeding stock exhibitions and sports happenings, with lectures, seminars, and conferences. These features make this kind of agricultural exhibitions a suitable place for survey and data collection (Caffaro, Micheletti Cremasco, Roccato, & Cavallo, ; Cavallo, Görücü, & Murphy, ; Ferrari, Spinelli, Cavallo, & Magagnotti, ; Reichardt & Jürgens, ; Reichardt, Jürgens, Klöble, Hüter, & Moser, ).…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 conferences. These features make this kind of agricultural exhibitions a suitable place for survey and data collection (Caffaro, Micheletti Cremasco, Roccato, & Cavallo, 2018;Cavallo, Görücü, & Murphy, 2015;Ferrari, Spinelli, Cavallo, & Magagnotti, 2012;Reichardt, Jürgens, Klöble, Hüter, & Moser, 2009).…”
Section: Participants and Settingmentioning
confidence: 99%
“…Since the agricultural population is spread across the country and has varying operating schedules, agricultural machinery exhibitions are one of the best occasions where a large and wide-ranging group of farmers, agricultural workers and other agricultural business operators come together. Therefore, such events provide a suitable place to conduct surveys and other data collection activities [24,38,42,43].…”
Section: Participants and Settingmentioning
confidence: 99%
“…The survey was carried out in the Piedmont region, Northwestern Italy, and it involved a non-random sample of farm operators, selected among the visitors of an agricultural exhibition. Previous studies have shown that farmers from the Piedmont can be usefully surveyed to analyze the dynamics of the Italian farming population [42,43].…”
Section: Limitations Of the Present Study And Possible Research Develmentioning
confidence: 99%
“…Currently, GNSS [4][5][6] and ISOBUS [7,8] based fleet management are widely used and can realize real-time visibility of vehicle location, status, and diagnostics. However, it cannot record subtle but important operating behaviors [9] , such as longtime stalling or idling, sudden acceleration, sharp turning, and etc. [10] .…”
Section: Introduction mentioning
confidence: 99%